2021
DOI: 10.1038/s41598-021-99471-x
|View full text |Cite
|
Sign up to set email alerts
|

A millisecond passive micromixer with low flow rate, low sample consumption and easy fabrication

Abstract: Fast mixing of small volumes of solutions in microfluidic devices is essential for an accurate control and observation of the dynamics of a reaction in biological or chemical studies. It is often, however, a challenging task, as the Reynolds number (Re) in microscopic devices is typically < 100. In this report, we detail a novel mixer based on the “staggered herring bone” (SHB) pattern and “split-recombination” strategies with an optimized geometry, the periodic rotation of the flow structure can be control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 66 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…In this case, the geometry of the microfluidic system will be more complex and passive, or active separation structures can be added to the chip [ 57 , 58 ]. For labelled techniques, the microfluidic chip can be expanded with microfluidic mixers [ 59 ] to blend the material under test (MUT) with fluorescent components or nanoparticles. In this review, we focus on label-free detection of proteins in biological fluids, so we will not delve into the components for manipulation.…”
Section: Methods For Manufacturing Microfluidic Structures For Biosen...mentioning
confidence: 99%
“…In this case, the geometry of the microfluidic system will be more complex and passive, or active separation structures can be added to the chip [ 57 , 58 ]. For labelled techniques, the microfluidic chip can be expanded with microfluidic mixers [ 59 ] to blend the material under test (MUT) with fluorescent components or nanoparticles. In this review, we focus on label-free detection of proteins in biological fluids, so we will not delve into the components for manipulation.…”
Section: Methods For Manufacturing Microfluidic Structures For Biosen...mentioning
confidence: 99%
“…Better mixing was achieved in a short distance while using a circular channel with high number of tall wall structure and it act as an obstacles. Y. Liao et al 25 reported a passive micromixer device with staggered herring bone structure and split–recombination microchannel. The mixing efficiency was analysed using a wide range of flow rates, 1–12 μL min −1 , and Reynolds numbers 3.3–40 and they achieved 98% mixing efficiency at 4.5–78 milliseconds.…”
Section: Introductionmentioning
confidence: 99%
“…Many micromixers used in the biological and chemical applications operate usually in the range of millisecond mixing time, and the corresponding Reynolds number is less than about 100 [ 28 , 29 , 30 ]. In this range, the mixing mechanism is usually divided into three regimes: molecular dominance, transition, and convection dominance [ 18 , 26 ].…”
Section: Introductionmentioning
confidence: 99%